2019
DOI: 10.3389/fchem.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Aptamers on Graphene Oxide for Efficient Inhibition of Thrombin Activity

Abstract: Graphene oxide (GO), a two-dimensional material with a high aspect ratio and polar functional groups, can physically adsorb single-strand DNA through different types of interactions, such as hydrogen bonding and π-π stacking, making it an attractive nanocarrier for nucleic acids. In this work, we demonstrate a strategy to target exosites I and II of thrombin simultaneously by using programmed hybrid-aptamers for enhanced anticoagulation efficiency and stability. The targeting ligand is denoted as Supra-TBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…In the past decades, both serendipity and targeted rational design have contributed to discover chemically modified TBA analogues endowed with markedly improved physico-chemical and biological properties. Among the approaches thus far explored to obtain modified TBA variants with promising pharmacokinetic profiles, either backbone modifications [7][8][9][10][11][12][13][14][15][16][17][18][19] or incorporation onto suitable nanoplatforms -including magnetic, [20][21][22] gold, [23][24][25][26][27] silica-based nanoparticles [28][29][30][31] and graphene [32,33] -have been successfully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, both serendipity and targeted rational design have contributed to discover chemically modified TBA analogues endowed with markedly improved physico-chemical and biological properties. Among the approaches thus far explored to obtain modified TBA variants with promising pharmacokinetic profiles, either backbone modifications [7][8][9][10][11][12][13][14][15][16][17][18][19] or incorporation onto suitable nanoplatforms -including magnetic, [20][21][22] gold, [23][24][25][26][27] silica-based nanoparticles [28][29][30][31] and graphene [32,33] -have been successfully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…However, many exhibit poor specificity and affinity, a short half-life, and susceptibility to nuclease present in the cell and blood, which limits their widespread applications in vivo. A recent study reported that nanocomposites and hybrid aptamer-immobilized GOx effectively inhibit thrombin’s coagulant activity in the blood [ 121 ]. This hybrid aptamer comprises two different aptamers (a 15-mer and a 29-mer) against thrombin that are linked with multiple poly (adenine) (A 20 ) segments.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In this context, TBA15 was incorporated onto very different nanoplatforms, including magnetic [ 126 , 127 , 128 ], gold [ 129 , 130 , 131 , 132 , 133 ], silica-based nanoparticles [ 134 , 135 , 136 , 137 ], and graphene [ 138 , 139 ].…”
Section: Anticoagulant Aptamersmentioning
confidence: 99%